Associations of breast cancer risk factors with tumor subtypes: a pooled analysis from the Breast Cancer Association Consortium studies - Yang, Xiaohong Rose; Chang-Claude, Jenny; Hamann, Ute; Hein, Rebecca; Vrieling, Alina; Sinn, Peter (Journal of the National Cancer Institute, 2011)
Previous studies have suggested that breast cancer risk factors are associated with estrogen receptor (ER) and progesterone receptor (PR) expression status of the tumors.We pooled tumor marker and epidemiological risk factor data from 35 568 invasive breast cancer case patients from 34 studies participating in the Breast Cancer Association Consortium. Logistic regression models were used in case-case analyses to estimate associations between epidemiological risk factors and tumor subtypes, and case-control analyses to estimate associations between epidemiological risk factors and the risk of developing specific tumor subtypes in 12 population-based studies. All statistical tests were two-sided. In case-case analyses, of the epidemiological risk factors examined, early age at menarche (≤12 years) was less frequent in case patients with PR − than PR + tumors ( P = .001). Nulliparity ( P = 3 × 10 −6 ) and increasing age at first birth ( P = 2 × 10 −9 ) were less frequent in ER − than in ER + tumors. Obesity (body mass index [BMI] ≥ 30 kg/m 2 ) in younger women (≤50 years) was more frequent in ER − /PR − than in ER + /PR + tumors ( P = 1 × 10 −7 ), whereas obesity in older women (>50 years) was less frequent in PR − than in PR + tumors ( P = 6 × 10 −4 ). The triple-negative (ER − /PR − /HER2 − ) or core basal phenotype (CBP; triple-negative and cytokeratins [CK]5/6 + and/or epidermal growth factor receptor [EGFR] + ) accounted for much of the heterogeneity in parity-related variables and BMI in younger women. Case-control analyses showed that nulliparity, increasing age at first birth, and obesity in younger women showed the expected associations with the risk of ER + or PR + tumors but not triple-negative (nulliparity vs parity, odds ratio [OR] = 0.94, 95% confidence interval [CI] = 0.75 to 1.19, P = .61; 5-year increase in age at first full-term birth, OR = 0.95, 95% CI = 0.86 to 1.05, P = .34; obesity in younger women, OR = 1.36, 95% CI = 0.95 to 1.94, P = .09) or CBP tumors. This study shows that reproductive factors and BMI are most clearly associated with hormone receptor-positive tumors and suggest that triple-negative or CBP tumors may have distinct etiology.